Karakter dalam Cerita Wayang Kumbakarna Gugur - Yudi Permana (Pascasarjana ISBI Bandung, 2019)
The values of life are inherent on arts, likewise on Wayang. Characters of Wayang seem to have human characteristics. One of them is the character of Kumbakarna in the play of Kumbakarna Gugur that will be analysed with narrative analysis method. Kumbakarna is considered as an evil character but he is willing to sacrifi ce himself to defend his kingdom not to rescue his brother, Rahwana. The character of Kumbakarna is ambivalent when on one side he fi ghts for his brother to get Shinta, but on the other side he realizes that what he does is an evil deed. He knows that Rahwana does not have his right to have Shinta. However, Rahwana’s happiness is in confl ict with Shinta’s suff ering.Keywords: Wayang, Kumbakarna Gugur, ambivalence, narrative analysis